Peningkatan Pengetahuan dan Keterampilan Ecoprint Sebagai Upaya Pengembangan Kreativitas dan Produk Ramah Lingkungan - Riski Wulandari Hutagaol; Intan Zatura; Novi Hendri Adi; Atman Lucky Fernandes; Amelia Rachmi Nasution; Yera Wahda Wahdi (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The use of synthetic chemical dyes in the textile and home-based batik industries remains a serious environmental issue due to wastewater pollution and its impact on public health. This community service program aimed to provide training on the steaming ecoprint technique as an environmentally friendly dyeing method while fostering creative economic opportunities for housewives. The program employed socialization, demonstrations, and hands-on practice. The results showed an increase in the Respondent Achievement Level (TCR) from 77.98% to 87.18%, with improvements in basic ecoprint knowledge (75.50%–87.45%), production skills (78.46%–89.70%), and entrepreneurial attitude and interest (80.00%–82.73%). The training effectively improved participants' knowledge and skills and is expected to encourage the development of environmentally friendly creative businesses in Kampung Tengah, Nongsa District, Batam City.